EJAKULASI PREMATUR SEBAGAI ALASAN PERCERAIAN MENURUT KOMPILASI HUKUM ISLAM (KHI) DAN FIQH SYAFI’IYAH - Nurhayati Zein (Marwah: Jurnal Perempuan, Agama dan Jender, 2012)
One of the sexual harassment experienced by the husband is premature ejaculation. This disorders can distrub the harmonisation of husband-wife relationship because one is experiencing premature ejaculation cannot give sexual satisfaction to his wife. Thus, the purpose of marriage is to establish sakinah, mawaddah and mercy familiy will not be realized due to unpay of the rights and obligations. In the Compilation of Islamic Law, premature ejaculation is included as the reason for wife to ask divorce, in Islamic term it called ‘khulu’. While the Shafi’s mazhab, premature ejaculation can be as a reason to give fasakh. Although, ‘khulu “ and ‘fasakh” are icluded as the reasons for divorce , but both have different legal effects. In the hadith of ‘khulu’, it was said that ‘khulu’ does not do due to unperfect husband to fulfill the sexual need of wife or husbund leave his obligations. It is more ampasize on un pleasuare wife toward the husband which will ditrub the harmonisation in the household.